Multi-channel functional near-infrared spectroscopy for real-time monitoring during carotid artery stenting: a case series - Gu, Xin; Chen, Yun-Hsuan; Shao, Anwen; Yin, Congguo; Sawan, Mohamad; Liu, Keqin (Frontiers in Neuroscience, 2026)
Functional near-infrared spectroscopy (fNIRS) offers a non-invasive method to monitor cerebral oxygenation and hemodynamic changes in real time. Transient hemodynamic instability during carotid artery stenting (CAS) may compromise blood–brain barrier (BBB) integrity and cerebral homeostasis, highlighting the need for sensitive intraoperative monitoring. Compared with traditional dual-channel NIRS systems limited to the frontal region, multi-channel fNIRS enables spatially resolved assessment of cortical hemodynamics and may provide a valuable adjunct for cerebroprotection research. We retrospectively analyzed five consecutive patients who underwent CAS under local anesthesia, with continuous multi-channel fNIRS monitoring before, during, and after the procedure. Forty-five cortical channels covering bilateral anterior circulation were recorded. Changes in oxyhemoglobin concentration (Δ[OxyHb]) and its standard deviation around key procedural events were analyzed to evaluate cortical oxygenation dynamics. All five procedures were technically successful, reducing residual stenosis to less than 30%. fNIRS consistently revealed increased cortical oxygenation following angioplasty and stent deployment, indicating improved cerebral perfusion. In four patients, transient fluctuations in cortical oxygenation corresponded to perioperative hemodynamic instability, such as bradycardia or hypotension induced by carotid sinus reflex. In one patient, marked declines in cortical oxygenation preceded transient neurological deficits, with recovery parallel to blood pressure normalization. These findings suggest that multi-channel fNIRS can sensitively capture both global and regional alterations in cerebral oxygenation during CAS, providing real-time insight into perfusion dynamics potentially linked to BBB function and cerebroprotection. Future studies integrating fNIRS with BBB-targeted markers may help refine intraoperative neuroprotection strategies in stroke and vascular interventions.